Metformin attenuates hepatic insulin resistance in type-2 diabetic rats through PI3K/Akt/GLUT-4 signalling independent to bicuculline-sensitive GABAA receptor stimulation - Debapriya Garabadu; Sairam Krishnamurthy (Taylor & Francis Group, 2017)
Context: Metformin attenuates type-2 diabetes mellitus (T2DM)-induced hepatic dysfunction and altered PI3K/Akt/GLUT-4 signalling in experimental studies. However, its effect on bicuculline-sensitive gamma amino butyric acid (GABA)-A receptor (GABAAR)-mediated calcium-dependent PI3K/Akt/GLUT-4 signalling in liver challenged to T2DM has not been established. Objective: The effectiveness of metformin on bicuculline-sensitive GABAAR-mediated hepatic insulin signalling was carried out in presence or absence of bicuculline (2.0 mg/kg, i.p.) in experimental T2DM rats. Materials and methods: The whole experimental design was divided into three independent sets of experiments. Each set comprised seven groups of six male rats each. T2DM was induced in the animals by administering streptozotocin (45 mg/kg, i.p.) and nicotinamide (110 mg/kg, i.p.) at a time lag of 15 min except control group rats in three experiments. Metformin and/or bicuculline or wortmannin were administered once daily for one week from seventh day of streptozotocin injection in all the experimental sets. Results: Metformin attenuated T2DM-induced hyperglycaemia in glucose (40%) and insulin (50%) tolerance tests in rats. Metformin also attenuated T2DM-induced hyperglycaemia (40%), hyperinsulinaemia (30%), insulin resistance (50%) and β-cell dysfunction (300%) in the animals. Metformin did not attenuate T2DM-induced decrease in rat hepatic intracellular calcium. Further, metformin mitigated T2DM-induced decrease in hepatic phosphorylated Akt and GLUT-4 translocation in the animals. The anti-diabetic activity of metformin was abolished by wortmannin but not with bicuculline co-administration in T2DM animals. Discussion and conclusion: These results suggest that metformin ameliorated T2DM-induced hepatic insulin resistance through bicuculline-sensitive GABAA receptor-independent PI3K/Akt/GLUT-4 signalling pathway in animals.